2018
DOI: 10.1111/cid.12621
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and pattern of implant fractures: A long‐term follow‐up multicenter study

Abstract: Peri-implantitis-induced marginal and vertical bone loss and manufacturing-induced defects were considered to be major factors in IF. Therefore, using clinically verified implant systems and striving to minimize bone loss by preventing and actively treating peri-implantitis is essential to reduce IFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…To the best of our knowledge, this is the first survival analysis to identify risk indicators for internal connection implant fractures over 10 years. A preliminary study was conducted to evaluate implant fracture patterns (Lee, Kim, Jeong, Kim, & Lee, ). Nonetheless, there were some limitations because that study did not consider time to fracture and the possible interdependence of factors related to the presence of multiple implants per person.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first survival analysis to identify risk indicators for internal connection implant fractures over 10 years. A preliminary study was conducted to evaluate implant fracture patterns (Lee, Kim, Jeong, Kim, & Lee, ). Nonetheless, there were some limitations because that study did not consider time to fracture and the possible interdependence of factors related to the presence of multiple implants per person.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first survival analysis to identify risk indicators for internal connection implant fractures over 10 years. A preliminary study was conducted to evaluate implant fracture patterns (Lee, Kim, Jeong, Kim, & Lee, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Dental implants have been used for more than half a century and currently are a highly reliable treatment option for long-term replacement (10+ years) of missing teeth [1,2]. As a long-term prognosis-established treatment, incidences of mechanical complications, such as fractures on fixtures or abutment screws, and biological complications, such as peri-implantitis, will inevitably occur [3][4][5][6]. An accurate understanding of the efficacy of different implant brands and the identification of treatment status are important for continued implant maintenance management and for dealing with any complications that arise.…”
Section: Introductionmentioning
confidence: 99%
“…2 Recent studies have • Fernanda Pereira de Caxias 2 • Lisiane Cristina Bannwart 3 investigated the rates, pattern and potential risk of implant fractures. [6][7][8] Lee et al found lower risk of fractures in implants with wide-diameter microthreads, placed in patients with a history of bone graft, as well as those positioned in the mandibular anterior area. 6 Karl, Scherg and Grobecker-Karl reported that torque might be a risk factor for fracture in zirconia implants.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Lee et al found lower risk of fractures in implants with wide-diameter microthreads, placed in patients with a history of bone graft, as well as those positioned in the mandibular anterior area. 6 Karl, Scherg and Grobecker-Karl reported that torque might be a risk factor for fracture in zirconia implants. 8 However, the literature reports a low incidence of implant fractures, but when it occurs, it can cause difficult problems for patients and dentists.…”
Section: Introductionmentioning
confidence: 99%